Distribution of bovine herpesvirus type 1 in the nervous system of experimentally infected calves - Marin, Maia Solange; Leunda, Maria Rosa; Verna, Andrea Elizabeth; Morán, Pedro Edgardo; Odeon, Anselmo Carlos; Pérez, Sandra Elizabeth (Elsevier, 2019)
Bovine herpesvirus type 1 (BoHV-1) is responsible for respiratory and genital disease in cattle. BoHV-1 encephalitis is only occasionally reported. However, several cases of neurological disease have been recently attributed to BoHV-1. In this study, the distribution and pathological alterations caused by two BoHV-1 strains in the nervous system of experimentally infected calves during acute infection and reactivation are described. Calves were inoculated intranasally with BoHV-1 Los Angeles (BoHV-1.LA) or Cooper (BoHV-1.Cooper) strains. Acutely infected calves were euthanased at 6 days (BoHV-1.Cooper, n = 2) and 7 days post-inoculation (BoHV-1.LA, n = 2). Latently infected calves that were given dexamethasone to induce reactivation were euthanased at 2 days (BoHV-1.Cooper, n = 2) or 5 days (BoHV-1.LA, n = 2) after dexamethasone administration. Both BoHV-1 strains were isolated from the brains of acutely infected calves. Distribution of viral DNA in the neural tissues was similar for both strains. During reactivation, neither BoHV-1.LA nor BoHV-1.Cooper was isolated from any brain section or trigeminal ganglia in infected calves. Macroscopic lesions were not evident in any group. In BoHV-1.LA infected calves, microscopic lesions were found in the brain but not in the trigeminal ganglia. Microscopic lesions in the brain of BoHV-1.Cooper infected calves were not as evident as in BoHV-1.LA infected animals. However, mononuclear infiltrates and neuronophagia were present in trigeminal ganglia. The results of this study demonstrated that respiratory BoHV-1 strains are able to replicate and disseminate within the bovine nervous tissue and provide evidence of the neuroinvasiveness of BoHV-1 strains.